Pengaruh Persepsi tentang Kompetensi Pedagogik Guru dan Kebiasaan Belajar Siswa terhadap Prestasi Belajar Matematika - Lambok Simamora (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2014)
The general objective of this research is to find and analyze empirically the influence of students' perceptions of pedagogical competence of teachers and learning habits of students together to learn mathematics achievement. Influence student perception of pedagogical competence of teachers to learn mathematics achievement and learning habits influence students to learn mathematics achievement. The research design used by the three variable regression technique which consists of two independent variables, namely the perception of students about the pedagogical competence of teachers and students' learning habits and the dependent variable, namely the achievement of learning Mathematics. The resulting regression equation Y = -207 + 1.37 X1 + 1.54 X2 with a correlation coefficient of 0.919 and a coefficient of determination 0.844 or 84.4%. It can be interpreted that the higher the students 'perceptions of teachers' pedagogical competence the better the learning achievement of the higher math and study habits, the higher the student achievement of learning Mathematics.